Breast cancer presentation delays among Arab and national women in the UAE: a qualitative study. (December 2016) - Elobaid, Yusra; Aw, Tar-Ching; Lim, Jennifer N.W.; Hamid, Saima; Grivna, Michal
Abstract: Breast cancer (BC) is a disease that has improved prospects for survival if detected and treated early. Delayed help-seeking behavior, with poor survival as a consequence, is an important public health issue in the Middle East. More than 75% of breast cancer patients in the United Arab Emirates (UAE) seek medical advice after experiencing a sign or symptom of the disease and many seek such advice late. Our aim was to explore factors influencing delayed presentation for treatment after self-discovery of symptoms consistent with breast cancer in Arab women in the United Arab Emirates (UAE), and to explore facilitators and barriers of women's health seeking behavior in the complex religiously dominated society of the UAE. A qualitative descriptive approach using semi-structured interviews was used. We interviewed nineteen BC survivors aged 35–70 who have experienced delayed presentation to treatment after symptomatic recognition of BC. The time interval between initial experience of symptoms consistent with BC, and taking action to seek medical help was between three months to three years. The key themes that emerged from the interviews were varying responses to symptom recognition, fear of societal stigmatization, and concerns regarding abandonment by spouse because of BC. Culture has a strong influence on the decisions of women in the UAE society. The lack of awareness about signs and symptoms of BC and routine screening has an important effect on symptom appraisal and subsequently decision making regarding options for treatment. Highlights: Lack of awareness about breast health, screening, signs/symptoms and risk factors. Culture/societal values have great influence on women׳s attitudes and behaviors. Support of healthcare providers may reduce likelihood of delay.